2020
DOI: 10.1080/19942060.2020.1830858
|View full text |Cite
|
Sign up to set email alerts
|

Monthly streamflow prediction using a hybrid stochastic-deterministic approach for parsimonious non-linear time series modeling

Abstract: wing Chau (2020) Monthly streamflow prediction using a hybrid stochastic-deterministic approach for parsimonious non-linear time series modeling, Engineering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Time series observations can often exhibit correlations with different degrees of non-linearity (Figure 3). This type of behavior is present in almost all real-world time series data, such as in stream-flow forecasting (Wang et al 2020), and in financial markets forecasting (Bukhari et al 2020).…”
Section: Stochastic Behaviormentioning
confidence: 94%
“…Time series observations can often exhibit correlations with different degrees of non-linearity (Figure 3). This type of behavior is present in almost all real-world time series data, such as in stream-flow forecasting (Wang et al 2020), and in financial markets forecasting (Bukhari et al 2020).…”
Section: Stochastic Behaviormentioning
confidence: 94%
“…To prevent the models from overfitting and underfitting, the objective function for improved GWO-GRU was to minimize the mean value of calibration loss and test loss when the difference of two losses was found within 0.005. In addition, the sequential IGWO-GRU model for five types of output (6,12,24,36, and 72 streamflow values for output, respectively) forecasting with four types of inputs (Ma, Mb, Mc, and Md) was determined by ACF and PACF [38], as shown in Table 2. The main procedure of PACF and ACF are (1) Make PACF and ACF plot with 95% confidence bands.…”
Section: Model Developmentmentioning
confidence: 99%
“…To date, scholars have developed a number of forecasting models using data-driven approaches, such as ANN (artificial neural network) and GEP (gene expression programming), to emulate hydrological behavior because it requires the least information [5,6]. ANN is a widely used model with good performance in comparison to traditional regression models [7].…”
Section: Introductionmentioning
confidence: 99%
“…The research showed that the hybrid SETAR-GEP model performed more optimally than the hybrid ARCH-GEP models for the prediction of the monthly streamflow of four rivers. Also, findings proposed several datapreprocessing tasks such as variational mode decomposition (VMD), complete ensemble empirical mode decomposition (CEEMD), and improved CEEMD as data decomposition methods to improve streamflow prediction [27]. Another study revealed that internal pressure is a critical factor for forecasting the discharge coefficient of inflatable dams [28].…”
Section: Introductionmentioning
confidence: 99%